Clinico-epidemiological nature and antibiotic susceptibility profile of Acinetobacter species - Biglari, Shirin (Professional Medical Publicaitons, 2013)
Objectives: Acinetobacter spp. has emerged as an important opportunistic pathogen responsible for nosocomial infections in many health-care settings worldwide. The study describes the clinico-epidemiology and antimicrobial susceptibility of Acinetobacter spp. in a tertiary health-care institution. Methodology: Acinetobacter spp. were isolated from 141 specimens of the patients who reported to Universiti Kebangsaan Medical Centre (UKMMC). The sources of specimens were wound, skin and soft tissue, respiratory and urinary tract from patients in various wards. Clinio-epidemiological features of patients infected with Acinetobacter spp. were recorded. Standard bacteriological techniques with API 20NE kits and disk diffusion method were followed for identification and antibiotic sensitivity of the organisms. Results: One hundred and forty one patients with positive culture for Acinetobacter spp. were identified. Soft tissue/wound and respiratory tract were among the commonest sites of Acinetobacter spp. isolation. The isolates were most frequently obtained from ICU. All isolates were multi-drug resistant and had a resistance rate of more than 70% to most antibiotics, except polymyxin B. Conclusion: High prevalence of multi-drug resistance Acinetobacter spp. provides essential information on judicious antibiotic selection for empirical therapy in our health-care institution.